Implementation of Independent Curriculum in Civics Education and Pancasila Subjects at SMA Negeri 1 Pringgabaya - Mahendra, Wisnu; Yuliatin, Yuliatin; Alqadri, Bagdawansyah; Zubair, Muh. (Journal of Educational Sciences, 2024)
The independent curriculum is a learning curriculum related to interests and talents for the improvement of the 2013 curriculum. One of the schools that implements an independent curriculum is SMA Negeri 1 Pringgabaya. This study aims to identify the implementation of independent curriculum in Civics Education and Pancasila subjects at SMA Negeri 1 Pringgabaya, what are the factors that affect the implementation of independent curriculum in Civics Education and Pancasila subjects at SMA Negeri 1 Pringgabaya. This research method uses a qualitative research approach method. The results showed that independent curriculum in Civics Education and Pancasila subjects at SMA Negeri 1 Pringgabaya has been implemented with the flow of Civics Education and Pancasila learning objectives, Civics Education and Pancasila teaching modules and Civics Education and Pancasila learning assessments, as well as supporting and inhibiting factors that influence the implementation of independent curriculum in Civics Education and Pancasila subjects at SMA Negeri 1 Pringgabaya. It can be concluded that independent curriculum in Civics Education and Pancasila subjects at SMA Negeri 1 Pringgabaya is implemented with the flow of learning objectives, teaching modules and learning assessments, as well as the factors that influence it.